Interleukin-6-Mediated-Ca2+ Handling Abnormalities Contributes to Atrial Fibrillation in Sterile Pericarditis Rats - Liao, Jie; Zhang, Shaoshao; Yang, Shuaitao; Lu, Yang; Lu, Kai; Wu, Yuwei; Wu, Qiongfeng; Zhao, Ning; Dong, Qian; Chen, Lei; Du, Yimei (Frontiers in Immunology, 2021)
Pre-existing Ca2+ handling abnormalities constitute the arrhythmogenic substrate in patients developing postoperative atrial fibrillation (POAF), a common complication after cardiac surgery. Postoperative interleukin (IL)-6 levels are associated with atrial fibrosis in several animal models of POAF, contributing to atrial arrhythmias. Here, we hypothesize that IL-6-mediated-Ca2+ handling abnormalities contribute to atrial fibrillation (AF) in sterile pericarditis (SP) rats, an animal model of POAF. SP was induced in rats by dusting atria with sterile talcum powder. Anti-rat-IL-6 antibody (16.7 μg/kg) was administered intraperitoneally at 30 min after the recovery of anesthesia. In vivo electrophysiology, ex vivo optical mapping, western blots, and immunohistochemistry were performed to elucidate mechanisms of AF susceptibility. IL-6 neutralization ameliorated atrial inflammation and fibrosis, as well as AF susceptibility in vivo and the frequency of atrial ectopy and AF with a reentrant pattern in SP rats ex vivo. IL-6 neutralization reversed the prolongation and regional heterogeneity of Ca2+ transient duration, relieved alternans, reduced the incidence of discordant alternans, and prevented the reduction and regional heterogeneity of the recovery ratio of Ca2+ transient. In agreement, western blots showed that IL-6 neutralization reversed the reduction in the expression of ryanodine receptor 2 (RyR2) and phosphorylated phospholamban. Acute IL-6 administration to isolated rat hearts recapitulated partial Ca2+ handling phenotype in SP rats. In addition, intraperitoneal IL-6 administration to rats increased AF susceptibility, independent of fibrosis. Our results reveal that IL-6-mediated-Ca2+ handling abnormalities in SP rats, especially RyR2-dysfunction, independent of IL-6-induced-fibrosis, early contribute to the development of POAF by increasing propensity for arrhythmogenic alternans.